THE USE OF ELECTRONIC DOCUMENT MANAGEMENT AND REPORTING SYSTEMS BY LOGISTICS COMPANIES OF UKRAINE - MOROZ, Sergiy; ZABOLOTNA, Sofia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article explores the possibilities and ways of using information technologies for document management and electronic reporting at logistics enterprises. Theoretical approaches to understanding the goals and tasks of logistics information systems in transport technologies have been considered. The main information technology systems that change the logistics industry in modern conditions have been characterized, namely: RPA; chat bots; visualization; Artificial Intelligence; predictive analytics. The electronic technologies used for information provision in Ukrainian practice, the IT-Enterprise ERP system of JSC ‘Ukrposhta’ and the CRM system of the company ‘Epicentr K’ have been analyzed. Their characteristics and advantages of use have been defined. It have been found that the basis of the functional component of the modern information system is a single module of operations between the links of the logistics system, which determines the relationship between the functional divisions of the company (in terms of the implementation of logistics functions), intermediate links and consumers of the company’s products. The implementation of a logistics information system in the work of a logistics enterprise makes it possible: - to increase the efficiency of its work, achieve a high level of service for customers and ensure effective control; - to ensure a modern approach to the management of implementation processes and the organization of various types of events; - to monitor the efficiency of commercial operations; - to conduct an analysis of the profitability of the activity; - to increase the effectiveness of price policy, etc. The problems of the introduction of electronic document flow and reporting systems in Ukraine have been noted: - the problem of interoperability in electronic document flow; - lack of clear standards and requirements for electronic reporting, companies may hesitate to switch to this type of reporting; – constant changes in legislation and requirements can create difficulties for enterprises in implementing stable electronic reporting systems; - inconsistency of electronic reporting formats with global ones; high implementation costs; - concerns about data privacy and security can deter companies from switching to electronic reporting, especially when the security of information on the network is at stake.